Long-Term Treatment of Venous Thromboembolic Disease - Prins, Martin H.; Hutten, Barbara A.; Koopman, Maria M.W.; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
After an initial 5- to 10-day course of treatment with either unfractionated or low molecular weight heparin, secondary prophylaxis is usually prescribed to patients with venous thromboembolic disease for a variable period of time. The primary aim of both initial and secondary treatment is to prevent recurrent thrombotic events, including deep vein thrombosis and fatal pulmonary embolism. This objective has to be achieved at a minimal risk of bleeding. There is general consensus that the initial treatment should be with low molecular weight or unfractionated heparin. For secondary prophylaxis, however, there are currently several options. Among these are continued unfractionated heparin or low molecular weight heparin and oral vitamin K-antagonists. In addition, compression stockings and caval vein filters are available.In this chapter, we will first examine the available evidence for each of these options, then discuss the results of randomized trials that have studied the duration of secondary prophylaxis. Finally, we will attempt to synthesize this information using decision analytic techniques.